Management of electrical injuries - Vagholkar, Ketan; Murarka, Arpit; Shetty, Sandeeta; Vagholkar, Suvarna (International Surgery Journal, 2017)
With growing industrialization and mechanization of every household electrical injuries are becoming quite common. Electrical injuries are quite intricate with the damage caused. They cause not only external burns injury but a wide spectrum of visceral injuries which in many cases is difficult to diagnose and manage. Therefore, a sound understanding of the engineering aspects is pivotal in diagnosing and managing these cases. A brief review of the pathophysiology and management of electrical injuries is presented.